Effects of mobile phone radiation on buccal mucosal cells based on specific absorption rate: a cross sectional study - Revanth, M. P.; Aparna, S.; Madankumar, Parangimalai Diwakar; Ranganathan, K. (International Journal Of Community Medicine And Public Health, 2021)
Background: The usage of mobile phone had been increased drastically which created a major health concern among the people about the radiation emitted from mobile phones. Hence this study was aimed to evaluate the Micronuclei (MN) frequency in exfoliated oral mucosal cells in high and low mobile users based on Specific absorption rate (SAR) value. Methods: The total of 60 subjects were divided into two major groups: low SAR mobile phone users and high SAR mobile phone users. Further, Subjects who use mobile phone for more than 3 hours a week was considered as high talk time users and less than 3 hours a week was low talk time users. The buccal mucosa cells extracted by slightly scraping the oral cavity with a wooden spatula. For staining, Giemsa stain was used. Micronuclei were evaluated in 1000 cells per individual at the microscope. Results: The result show prolonged talk time may interfere with the development of micronuclei in individuals who use mobile phone for more than 3 hours per week rather than high SAR value showing a significant increase in frequency of micronuclei formation. Conclusions: The study showed mobile phone radiation had adverse effects on buccal mucosal cells.